(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This article analyzes the relevance of using modern pedagogical technologies in teaching the energy sector, their effectiveness in the educational process, and existing problems. The study demonstrates the advantages of implementing innovative teaching methods, digital technologies, 3D modeling, and virtual laboratories. Practical proposals for improving the educational process will also be provided.